Stogdill's Handbook of LeadershipStogdill's Handbook of Leadership, by Bass Bernard M. Free Press, 1981, 856 pp., $39.95 cloth. - McCall, Morgan W. (Academy of Management Review, 1982)
The article reviews the book ?Stogdill's Handbook of Leadership,? by Bernard M. Bass.